2014
DOI: 10.1111/ijsa.12074
|View full text |Cite
|
Sign up to set email alerts
|

Preselection Methods Prior to the Internal Assessment Center for Personnel Selection in German Companies

Abstract: Companies frequently use preselection methods in order to identify eligible candidates before conducting assessment centers (ACs). The present study was the first to investigate current practices of preselection in German companies that use ACs for internal selection. Results of a survey among 109 German companies show that companies typically apply general qualification criteria (e.g., work experience), appraisals, or unstructured interviews for preselection, but rely less on trait‐oriented methods (e.g., int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The recognition of talented current employees is most often based on managers’ proposals and the expression of a desire to develop in interviews conducted by HR. Similar to the German study ( Benit et al, 2014 ), a little less than one third of the participating companies use psychometric testing to identify talent, and even fewer use evaluation centers. Medium-sized companies report the use of a 9-box grid matrix, but the use is probably more appropriate at companies with fewer employees, as it could be extremely time-consuming at large companies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The recognition of talented current employees is most often based on managers’ proposals and the expression of a desire to develop in interviews conducted by HR. Similar to the German study ( Benit et al, 2014 ), a little less than one third of the participating companies use psychometric testing to identify talent, and even fewer use evaluation centers. Medium-sized companies report the use of a 9-box grid matrix, but the use is probably more appropriate at companies with fewer employees, as it could be extremely time-consuming at large companies.…”
Section: Discussionmentioning
confidence: 94%
“…Many companies when planning talent management think first of all about attracting talented individuals from the labor market, but pay less attention to using scientifically proven methods and approaches to recognizing talent ( Pulakos, 2005 ). A study conducted in Germany ( Benit et al, 2014 ) indicated that when selecting employees companies seldomly employ quality-oriented methods such as annual evaluation discussions, psychometric testing or evaluation centers. Some organizations use a 9-box grid to identify “high-potentials,” who are described as competent, engaged and striving to become leaders, and “high-performers,” who have already demonstrated such skills, viewpoints and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…According to the survey author, Henry Dennison, this is because ‘…no single simple method would suffice to discover and test the subtle and varied qualifications of men’ (National Bureau of Economic Research, ; p. 519). Nearly a century later, views about the usefulness of standardized tests have changed surprisingly little (Benit et al, ; Lodato et al, ; Rynes et al, ). This is despite the volumes of research suggesting that psychologists have achieved considerable success reducing error in the prediction of job performance (Schmidt & Hunter, ).…”
Section: Discussionmentioning
confidence: 99%
“…519). Nearly a century later, views about the usefulness of standardized tests have changed surprisingly little (Benit et al, 2014;Lodato et al, 2011;Rynes et al, 2002). This is despite the volumes of research suggesting that psychologists have achieved considerable success reducing error in the prediction of job performance (Schmidt & Hunter, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation